Exact non-stationary solution for the density matrix of single two-level atom - Enachi, Nicolae (D.Ghitu Institute of Electronic Engineering and Nanotechnologies, 2009)
The master equation for short- and long-time interaction intervals of single two-level atom with electromagnetic field vacuum for studying non-exponential emission is proposed.